Caries-Exclusive and Health-Associated Taxa in the Peruvian Pediatric Salivary Microbiome Identified by Full-Length Nanopore 16S Sequencing: Implications for Ecological Modulation of Dental Caries - Laly Abigail Rojas Rodríguez; Carlos Michell Gálvez Ramírez; Marco Aurelio Salvatierra Celis; Justo Nilo Balcazar Conde; Margarita Fé Requena Mendizábal; Rocio Del Pilar Bocanegra Arista; Roger Dámaso Calla Poma; Tania Valentina Rosales Cifuentes (Microorganisms, 2026)
Dental caries is the most prevalent chronic noncommunicable disease in Peruvian schoolchildren (>70%). Full-length 16S Oxford Nanopore Technology (ONT) sequencing enables species-level resolution unachievable with conventional Illumina V3–V4 platforms, critical for resolving intrageneric diversity in the dominant oral genus Streptococcus This is a cross-sectional study (STROBE/STORMS) of 30 children aged 8–10 years (15 with caries, ceod/CPOD ≥ 1; 15 caries-free, ceod/CPOD = 0) from IE N°3036 José Andrés Rázuri, San Martín de Porres, Lima, with caries status assessed by clinical examination using ICDAS-II criteria and summarized using the ceod/CPOD indices. Full-length 16S sequencing (~1500 bp; 27F/1492R; SQK-16S024) was performed on MinION MK1B (MN40465), with Flongle AUB828 in two runs (Run 1: 21,651 PASS reads, Q = 12.50; Run 2: 3750 PASS reads, Q = 11.89). The pipeline used was wf-16s v1.2.0 (EPI2ME, NCBI 16S rRNA), while for statistics, Mann–Whitney U test, Fisher’s exact test (α = 0.05), and PERMANOVA (999 permutations) were used. In total, 126 species were identified in 63 genera and 5 phyla. Streptococcus salivarius was dominant (22.5%; 30/30). Twenty-six species were exclusive to the caries group, led by S. mutans (7/15, 46.7%; OR = ∞; raw p = 0.006) and S. anginosus (4/15, 26.7%; OR = ∞; raw p = 0.038), plus Lancefieldella parvula, Veillonella infantium, and Actinomyces naeslundii. Fifteen species were exclusive to the healthy group, including Rothia aeria, Gemella sp., Aggregatibacter kilianii, and Bulleidia extructa. None of these taxon-level differences survived Benjamini–Hochberg correction for the 126 species tested (all FDR-adjusted p > 0.45); these findings are therefore presented as exploratory candidates rather than confirmed differences. Alpha diversity (Shannon p = 0.507) and global beta diversity (PERMANOVA p = 0.215) did not differ; dysbiotic convergence was significant (intragroup Bray–Curtis: 0.322 vs. 0.414; p < 0.001). This is the first ONT full-length 16S characterization of the salivary microbiome in Peruvian children, simultaneously identifying cariogenic and health-associated species profiles. These findings suggest dietary nitrate supplementation and xylitol as candidate prebiotic strategies warranting future intervention studies to restore health-associated taxa in caries-free children.